Commodity Transport Studies Limestone Planning Commission - Planning Commission (Planning Commission, 1965)
At the first meeting of the Planning Committee for Transport, held on July 2, 1963, it was decided that the Joint Technical Group should undertake, along with other studies, the analysis of the present and future patterns of movement of selected commodities so as to help in the formulation of the Fourth and Fifth Plans in the transport sector.
Joint Technical Group for Transport Planning, Planning Commission